Design and cost optimization for hierarchical data. (27th March 2014) - Tokola, Kari; Lundell, Andreas; Nevalainen, Jaakko; Oja, Hannu
<x xml:space="preserve">Abstract</x> In this paper, we consider balanced hierarchical data designs for both one‐sample and two‐sample (two‐treatment) location problems. The variances of the relevant estimates and the powers of the tests strongly depend on the data structure through the variance components at each hierarchical level. Also, the costs of a design may depend on the number of units at different hierarchy levels, and these costs may be different for the two treatments. Finally, the number of units at different levels may be restricted by several constraints. Knowledge of the variance components, the costs at each level, and the constraints allow us to find the optimal design. Solving such problems often requires advanced optimization tools and techniques, which we briefly explain in the paper. We develop new analytical tools for sample size calculations and cost optimization and apply our method to a data set on Baltic herring.